MT1-MMP controls human mesenchymal stem cell trafficking and differentiation - Lu, Changlian (American Society of Hematology, 2010)
Human mesenchymal stem cells (hMSCs) localized to bone marrow, nonhematopoietic organs, as well as perivascular niches are postulated to traffic through type I collagen-rich stromal tissues to first infiltrate sites of tissue damage, inflammation, or neoplasia and then differentiate. Nevertheless, the molecular mechanisms supporting the ability of hMSCs to remodel 3-dimensional (3D) collagenous barriers during trafficking or differentiation remain undefined. Herein, we demonstrate that hMSCs degrade and penetrate type I collagen networks in tandem with the expression of a 5-member set of collagenolytic matrix metalloproteinases (MMPs). Specific silencing of each of these proteases reveals that only a single membrane-tethered metalloenzyme, termed MT1-MMP, plays a required role in hMSC-mediated collagenolysis, 3D invasion, and intravasation. Further, once confined within type I collagen-rich tissue, MT1-MMP also controls hMSC differentiation in a 3D-specific fashion. Together, these data demonstrate that hMSC invasion and differentiation programs fall under the control of the pericellular collagenase, MT1-MMP.